2005
DOI: 10.1029/2004ja010985
|View full text |Cite
|
Sign up to set email alerts
|

Global thermospheric neutral density and wind response to the severe 2003 geomagnetic storms from CHAMP accelerometer data

Abstract: [1] Measurements of atmospheric density near 410 km from the STAR accelerometer on the CHAMP satellite are used to illustrate the spatial-temporal dependence of the thermospheric response to the severe solar storms occurring during 29 October to 1 November 2003. This interval includes periods of elevated magnetic activity with K P values of 5-9, as well as undisturbed intervals that serve to define quiet time baseline densities. Measurements are available from À87°to +87°latitude during both day and night at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
219
3
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 207 publications
(230 citation statements)
references
References 36 publications
6
219
3
2
Order By: Relevance
“…We have also considered geomagnetic activity prior to the CHAMP pass [cf. Aruliah et al, 1999], which can influence the thermospheric density [e.g., Sutton et al, 2005;Zhou et al, 2009] andcomposition [e.g., Crowley et al, 2006]. While the Kp ≤ 2 criterion was satisfied during and within the 3 h interval prior to the CHAMP pass, in both the cases where the ESR estimate was below that of the CHAMP measurement (cases 4 and 8), the Kp index had been raised to levels > 2 in the 24 h prior to the interval of the CHAMP measurement.…”
Section: Champ Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have also considered geomagnetic activity prior to the CHAMP pass [cf. Aruliah et al, 1999], which can influence the thermospheric density [e.g., Sutton et al, 2005;Zhou et al, 2009] andcomposition [e.g., Crowley et al, 2006]. While the Kp ≤ 2 criterion was satisfied during and within the 3 h interval prior to the CHAMP pass, in both the cases where the ESR estimate was below that of the CHAMP measurement (cases 4 and 8), the Kp index had been raised to levels > 2 in the 24 h prior to the interval of the CHAMP measurement.…”
Section: Champ Resultsmentioning
confidence: 99%
“…The reader is referred to Sutton et al [2005] and Sutton [2009] where descriptions of the force model used in the STAR accelerometer data processing and estimations of the total mass density can be found. The time resolution of the CHAMP data used was 10 s, which corresponds to a spatial separation of approximately 80 km between consecutive measurements along the satellite track.…”
Section: Champ Satellite Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] Sutton et al [2005] reported the following observations from CHAMP measurements: During the first stage of geomagnetic activity on 29 October 2003, on the dayside elevated density levels of the order of 300% could be seen at northern latitudes. On the nightside density enhancements last longer than on the dayside and can be seen to travel toward the equator.…”
Section: Introductionmentioning
confidence: 99%